Do We Have the Workforce Skills for Maine’s Innovation Economy? - Dorrer, John (Maine Policy Review, 2014)
A convergence of economic and demographic forces is shaping a set of formidable challenges for Maine. This article describes how a workforce with superior skills is the key to economic growth and innovation. Over the last five decades, skill requirements have changed dramatically for most workers with the shift from goods-producing to service industries. While much has been done in reforming K-12, post secondary, and adult education systems to accommodate the changing Maine economy, it is not enough More innovation and adaptation will be required from policymakers, institutional leaders, employers and Maine people themselves.